Análise das aplicações de metadados baseada em FRBR e RDA em repositórios institucionais digitais: contribuições do domínio bibliográfico - Cerrao, Natalia Gallo (2019)
Descriptive Cataloging goes through a moment of reflection and reorganization in search of its identity and has been studied in an increasingly interdisciplinary way by professionals from heterogeneous fields. In the bibliographic domain, with the development of conceptual models, such as the Functional Requirements for Bibliographic Records (FRBR) and the propose of Resource Description and Access (RDA) guidelines for resource description, it is necessary to understand how such initiatives relate to digital institutional repositories. The objective of this research was the study of FRBR and RDA established in the bibliographic domain, in order to identify the state of the art on the trends of the bibliographic domain and if they can be applied in digital institutional repositories. The theoretical and methodological support of the Systematic Literature Review (RSL) provided the mapping and identification of key elements to answer the research question. In addition, an empirical study was conducted in the Institutional Repository of the Federal University of Sergipe, from the analysis of a descriptive record that could be identified the theoretical and applied principles of FRBR and RDA. Twenty-five (25) documents were analyzed in the RSL, which can be considered a relatively low index on scientific production consistent with the research proposal and the need for further studies on the subject. Computational technologies, use cases and specific applications were identified in bibliographic, academic and Web environments. Through RSL it was possible to identify and analyze FRBR and RDA based metadata applications in digital institutional repositories, with the extraction of mapped theoretical and methodological requirements. by the international scientific literature. It is emphasized that the state of the art built in this research presents itself as a starting point for the development of tools and applications that bring the bibliographic domain closer to digital institutional repositories. Thus, the contributions of the bibliographic domain characterized in this context by FRBR and RDA and their application in digital institutional repositories can be evidenced in the transfer of concepts, processes, methods, instruments, technologies, models and patterns for the description of features from Descriptive Cataloging, favoring the modeling of open and interoperable environments and systems, providing more intuitive and accessible interfaces, ensuring the most optimized retrieval of information for users.